Characteristics of Atopic Bronchial Asthma in Seniors over 80 Years of Age. (30th July 2013) - Bożek, Andrzej; Filipowski, Marek; Fischer, Andreas; Jarzab, Jerzy
Abstract : Background . Asthma in the elderly is an important public health problem. The aim of this study was to assess the prevalence and characteristics of asthma in seniors. Materials and Methods . The study involved 105 people of at least 80 years of age (mean age of 84.1 ± 3.9 years) selected from a group of 1860 individuals. Spirometry, the methacholine test, allergy diagnosis, a measurement of exhaled nitric oxide, and administration of the asthma quality of life questionnaire (AQLQ) were performed. Results . The average morbidity of asthma in the study population of elderly people (at least 80 years of age) was 5.6% (105 people) of the confidence interval (95% CI: 5.1–6.0). In the study group, 34% of the elderly asthmatics had uncontrolled asthma, 47% had partly controlled asthma, and only 24% had fully controlled asthma. Allergy to house dust mites was predominant. The average total score on the AQLQ was 4.12 ± 0.72 (arithmetic mean ± standard deviation) for the seniors, which was significantly lower than the score for the young. Conclusion . The pathogenesis, natural history, and value of the basic diagnostic methods of asthma in the elderly are similar to those observed in younger age groups.